Structural, Optical and Antimicrobial Properties of Carbohydrate-Capped Cadmium Sulfide Nanoparticles - Adhikari, Subhav; Parajuli, Kshama; Karki, Guna B.; Khatiwada, Shankar P.; Adhikari, Rameshwar (Journal of Nepal Chemical Society, 2023)
Cadmium sulfidenanoparticles (CdSNPs) were prepared through the chemical precipitation process where sweet potato starch and glucose-functioned as capping agents. Ultraviolet-Visible (UV-Vis) spectroscopy, Fourier Transform Infrared (FTIR) spectroscopy and X-ray diffraction (XRD) techniques were applied for the analysis of prepared CdSNPs. The absorption peaks in the UV-Vis spectroscopy towards the lower wavelength region compared to the bulk CdS (512 nm) indicated the formation of CdS particles in the nanometer scale range. FTIR spectroscopy showed the characteristic absorption peaks of the CdSNPs along with the functional groups present in starch and glucose, suggesting the possible interaction between CdSNPs and capping agents. The XRD revealed crystallographic information such as the average crystallite size and shape of CdSNPs. Using the Scherrer equation, the average crystallite size of CdSNPs was determined to be 11.48 nm and 16.03 nm for starch-capped and glucose-capped CdSNPs (CdS-St andCdS-Gl)respectively. Antibacterial and antifungal activities of the prepared CdSNPs were found to be highly efficient for various pathogenic bacteria and fungi. Hence in the present study, the new synthetic route of CdSNPs was applied, and antimicrobial activities were performed